OLED display fundamentals and applications - Tsujimura, Takatoshi (Hoboken, New Jersey : John Wiley & Sons Inc., 2017)
'This book covers the aspects necessary to the design and manufacturing of OLED displays. Topics include emission mechanism, material selection, device processing, manufacturing issues and countermeasures and display design basics. In addition, the book defines elements of OLED such as Thin Film Transistor (TFT) backplane design and processing details, including Low Temperature Poly Silicon (LTPS) process and circuit integration, and high yield method to manufacturer. Researchers and developers are aiming at making large OLED televisions and companies such as Samsung and Apple are rumored to be using OLED display for new screens. In addition to discussing the current composition of OLED, the book also discusses the future for OLED technologies and displays. The new edition examines the most recent information available and also reinforces the content of the previous edition'--
'This book covers the aspects necessary to the design and manufacturing of OLED displays'--
3.2.2.3 Monitoring Thickness Using a Quartz Oscillator3.3 Encapsulation; 3.3.1 Dark Spot and Edge Growth Defects; 3.3.2 Light Emission from the Bottom and Top of the OLED Device; 3.3.3 Bottom Emission and perimeter sealing; 3.3.4 Top Emission; 3.3.5 Encapsulation Technologies and Measurement; 3.3.5.1 Thin-Film Encapsulation; 3.3.5.2 Face Sealing Encapsulation; 3.3.5.3 Frit Encapsulation; 3.3.5.4 WVTR Measurement; 3.4 Problem Analysis; 3.4.1 Ionization Potential Measurement; 3.4.2 Electron Affinity Measurement; 3.4.3 HPLC Analysis; 3.4.4 Cyclic Voltammetry; References
Includes bibliographical references and index.
Print version record.
Keywords: Flat panel displays; Electrtoluminescent devices; Organic semiconductors; Light emitting diodes; TECHNOLOGY & ENGINEERING / Electronics / General; TECHNOLOGY & ENGINEERING / Mechanical; Electronic books